RUSSIAN PRESCHOOL EDUCATION SYSTEM. - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
The article discusses about the Russian preschool education system, teaching skills, characteristics, quality of the educational process, opportunities and principles of the educational process in preschool educational institutions.